DETERMINAN KUALITAS AUDIT DI KANTOR AKUNTAN PUBLIK JAKARTA TIMUR - Alya Lena; M. Nurrasyidini; Daram Heriansyah (Jurnal Penelitian Ekonomi Akuntansi, 2021)
The purpose of This study is to study the effect of accounting knowledge, auditor experience, auditor independence, and auditor integrity on audit quality in East Jakarta public accounting firms. The method used in this research is quantitative method, where the variables studied are accounting knowledge, auditor experience, auditor independence and auditor integrity as independent variables and Audit Quality as the dependent variable. The population used in this study were all public accounting firms registered in the East Jakarta area. The sample selection technique used purposive sampling and the data were collected using a questionnaire and processed using SPSS software. Data processing and analysis techniques used in this study are accounting analysis, descriptive statistical analysis, data quality test, multiple linear regression analysis, classical assumption test, hypothesis testing and coefficient of determination. The results of the study show that Accounting Knowledge, Auditor Experience, Auditor Independence, and Auditor Integrity have an influence on the dependent variable (Audit Quality).